Exploring the Impact of Digital Technology on Indigenous Language Teaching and learning: A case study of the Igbo language - Okafor, Amaka Yvonne (International Journal of Administration and Education, 2025)
The rapid advancement of digital technology has opened new opportunities for the teaching and learning of indigenous languages, including the Igbo language. This study used a qualitative research approach, focusing on a literature review and document analysis to explore the impact of digital technology on Igbo language teaching and learning. It synthesized academic sources, reports, and case studies to understand how digital tools, such as mobile apps and online platforms, contributed to Igbo language preservation and revitalization. key themes identified and synthesized to highlight trends in the use of technology in Igbo language education. The research highlighted the role of technological innovations like iSabi Igbo+, Learn Igbo - EuroTalk, and NKENNE in enhancing the learning experience, making Igbo language education more accessible and engaging. The study revealed that digital tools offer flexible learning options, expand access to learning materials, and nurture greater cultural connection among younger generations. The study concluded with recommendations for policymakers, educators, and technology developers to focus on improving access to digital resources, enhancing teacher training, and promoting collaboration to ensure the sustainability and growth of the Igbo language in the digital era.